Efeitos da extens??o de marca vertical na luxuosidade percebida - Pimenta, Renato Ferreira (2016)
Submitted by Nadir Basilio (nadirsb@uninove.br) on 2016-06-06T20:37:04Z No. of bitstreams: 1 Renato Ferreira Pimenta.pdf: 943887 bytes, checksum: cb52869fbbd938da84da184a210a0987 (MD5)